Енергоефективність у системі економічної, енергетичної та екологічної безпеки країни та підходи до її вимірювання на підприємствах - Филюк, Галина Михайлівна; Шимченко, Н. В. (Київський національний університет імені Тараса Шевченка, 2025)
У статті досліджується роль енергоефективності в системі економічної, енергетичної та екологічної безпеки України в умовах повномасштабної війни та євроінтеграційних процесів. Проаналізовано поняття енергоефективності згідно різних наукових підходів. Виокремлено вплив енергоефективності на різні складові національної безпеки: зниження собівартості продукції та підвищення конкурентоспроможності підприємств у контексті економічної безпеки; зменшення залежності від імпорту енергоносіїв як чинник енергетичної безпеки; скорочення викидів парникових газів та негативного впливу на довкілля в рамках екологічної безпеки. Здійснено порівняльний аналіз індексів енергоємності України та країн ЄС, який виявив значне відставання вітчизняної економіки та підтвердив наявність потенціалу для підвищення ефективності використання енергоресурсів. Досліджено міжнародний досвід реалізації енергоефективної політики, зокрема принцип "Energy Efficiency First" у рамках European Green Deal, національні програми Німеччини та Польщі. Систематизовано інструменти та індикатори вимірювання енергоефективності на рівні підприємств відповідно до технічного, економічного, екологічного та соціально-організаційного підходів до управління. Обґрунтовано необхідність комплексного поєднання кількісних та якісних методів оцінювання для забезпечення обґрунтованості управлінських рішень щодо модернізації виробництва та впровадження енергозберігаючих технологій.

The article examines the role of energy efficiency in Ukraine's economic, energy, and environmental security in the context of full-scale war and European integration processes. The concept of energy efficiency is analyzed according to various scientific approaches. The impact of energy efficiency on various components of national security is highlighted: reducing production costs and increasing the competitiveness of enterprises in the context of economic security; reducing dependence on energy imports as a factor of energy security; reducing greenhouse gas emissions and negative environmental impact in the context of environmental security. A comparative analysis of the energy intensity indices of Ukraine and EU countries was carried out, which revealed a significant lag in the domestic economy and confirmed the potential for improving the efficiency of energy use. International experience in implementing energy efficiency policies was studied, in particular the “Energy Efficiency First” principle within the European Green Deal, and national programs in Germany and Poland. The tools and indicators for measuring energy efficiency at the enterprise level were systematized in accordance with technical, economic, environmental, and socio-organizational approaches to management. The article systematically categorizes the tools and indicators for measuring EE at the enterprise level, aligning them with technical, economic, environmental, and socio-organizational management approaches. It substantiates the necessity of a comprehensive combination of quantitative and qualitative assessment methods to ensure sound management decisions regarding production modernization, implementation of energy-saving technologies, development of a corporate culture of rational resource use, and boosting internal resilience. Collectively, these measures contribute to strengthening the nation's overall security.
Energy Efficiency in the System of Economic, Energy, and Environmental Security of the Country and Approaches to Its Measurement at Enterprises
Keywords: енергоефективність; енергетична безпека; енергозбереження; енергоємність; економічна безпека; екологічна безпека; вимірювання енергоефективності; energy efficiency; energy security; energy conservation; energy intensity; economic security; environmental security; energy efficiency measurement